Proceedings of the Twenty-Third Annual ACM-SIAM Symposium on Discrete Algorithms 2012
DOI: 10.1137/1.9781611973099.40
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Graph Structure via Linear Measurements

Abstract: We initiate the study of graph sketching, i.e., algorithms that use a limited number of linear measurements of a graph to determine the properties of the graph. While a graph on n nodes is essentially O(n 2 )-dimensional, we show the existence of a distribution over random projections into d-dimensional "sketch" space (d n 2 ) such that the relevant properties of the original graph can be inferred from the sketch with high probability. Specifically, we show that:including connectivity, k-connectivity, bipartit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
244
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(244 citation statements)
references
References 33 publications
0
244
0
Order By: Relevance
“…1. Statistical problems: computing the number of distinct elements, known as F 0 in the database literature; and finding the element with the maximum frequency, known as the ∞ or iceberg query problem.…”
Section: Our Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Statistical problems: computing the number of distinct elements, known as F 0 in the database literature; and finding the element with the maximum frequency, known as the ∞ or iceberg query problem.…”
Section: Our Resultsmentioning
confidence: 99%
“…For graph problems, Ahn, Guha and McGregor [1,2] developed an elegant technique for sketching graphs, and showed its applicability to many graph problems including connectivity, bipartiteness, and minimum spanning tree. Each sketching step in these algorithms can be implemented in the message-passing model as follows: each site computes a sketch of its local graph and sends its sketch to P 1 .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This use of linear projections is well-studied in the context of processing numerical data, e.g., signal reconstruction in compressed sensing [5,8], Johnson-Lindenstrauss style dimensionality reduction [1,12], and estimating properties of the frequency vectors that arise in data stream applications [7,13]. However, it is only recently that it has been shown that this technique can be applied to more structured data such as graphs [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that there exist O( −2 n polylog n)-dimensional sketches from which a combinatorial sparsifier can be constructed [2,3]. This naturally gave rise to the first data stream algorithm for cut estimation when the stream is fully-dynamic, i.e., contains both edge insertions and deletions.…”
Section: Introductionmentioning
confidence: 99%